Health literacy and refugees' experiences of the health examination for asylum seekers – a Swedish cross-sectional study. (December 2015) - Wångdahl, Josefin; Lytsy, Per; Mårtensson, Lena; Westerling, Ragnar
Abstract Background The purpose of the health examination for asylum seekers in most countries is to identify poor health in order to secure the well-being of seekers of asylum and to guarantee the safety of the population in the host country. Functional health literacy is an individual's ability to read information and instructions about health and to function effectively as a patient in the health system, and comprehensive health literacy is an individual's competence in accessing, understanding, appraising and applying health information. Little is known about refugees' health literacy and their experiences of the health examination for asylum seekers. The purposes of the study were to investigate refugees' experiences of communication during their health examination for asylum seekers and the usefulness of that examination, and whether health literacy is associated with those experiences. Methods A cross-sectional study was made among 360 adult refugees speaking Arabic, Dari, Somali or English. Health literacy was measured using the Swedish Functional Health Literacy Scale and the short European Health Literacy Questionnaire. Experiences of communication and the usefulness of the health examination were measured in several questions. Associations were sought using univariate and multivariate statistical models. Results In the health examination for asylum seekers, a poor quality of communication was experienced by 36 %, receiving little information about health care by 55 %, and receiving little new knowledge by 41 % and/or help by 26 %. Having inadequate as compared to sufficient comprehensive health literacy was associated with the experience of a poorer quality of communication (OR: 9.64, CI 95 %: 3.25–28.58) and the experience of receiving little valuable health care information (OR: 6.54, CI 95 %: 2.45–17.47). Furthermore, having inadequate as compared to sufficient comprehensive health literacy was associated with the experience of not receiving new knowledge (OR: 7.94, CI 95 %: 3.00–21.06) or receiving help with health problems (OR: 8.07, 95 % CI: 2.50–26.07. Functional healthy literacy was not associated with experiences of HEA. Conclusion Refugees' experiences indicate that a low level of comprehensive health literacy can act as a barrier to fulfilling the purposes of the health examination for asylum seekers. Comprehensive health literacy seems to be of greater importance in that context than functional health literacy.